2005
DOI: 10.1126/science.1107075
|View full text |Cite
|
Sign up to set email alerts
|

Early Local Last Glacial Maximum in the Tropical Andes

Abstract: The local last glacial maximum in the tropical Andes was earlier and less extensive than previously thought, based on 106 cosmogenic ages (from beryllium-10 dating) from moraines in Peru and Bolivia. Glaciers reached their greatest extent in the last glacial cycle ∼34,000 years before the present and were retreating by ∼21,000 years before the present, implying that tropical controls on ice volumes were asynchronous with those in the Northern Hemisphere. Our estimates of snowline depression reflect about half … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
205
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(227 citation statements)
references
References 20 publications
21
205
0
1
Order By: Relevance
“…It is possible that NC9 and NC10 are dating 1-2 older advances and NCNE01 a younger advance, which reached the same place and added a new moraine to pre-existing moraines. The younger moraines aggregation on older moraines, could also be the cause of the dispersed ages in many Andean glacial sites, such as Cajamarca [45], Cordillera Blanca [29], Jeulla Raju [105], Huayhuash [106], Junín [28], Quelccaya ice cap [6,107], Carabaya [46], Huayna Potosí, Río Suturi and Huamaní Loma [39]; Coropuna [37,38]; (this work); Hualca Hualca [7], Cerro Tunupa [8], and Uturuncu volcano [9].…”
Section: The Glaciers Maximum Extension and The Polygenic Moraines Dementioning
confidence: 93%
“…It is possible that NC9 and NC10 are dating 1-2 older advances and NCNE01 a younger advance, which reached the same place and added a new moraine to pre-existing moraines. The younger moraines aggregation on older moraines, could also be the cause of the dispersed ages in many Andean glacial sites, such as Cajamarca [45], Cordillera Blanca [29], Jeulla Raju [105], Huayhuash [106], Junín [28], Quelccaya ice cap [6,107], Carabaya [46], Huayna Potosí, Río Suturi and Huamaní Loma [39]; Coropuna [37,38]; (this work); Hualca Hualca [7], Cerro Tunupa [8], and Uturuncu volcano [9].…”
Section: The Glaciers Maximum Extension and The Polygenic Moraines Dementioning
confidence: 93%
“…. TCN-based chronologies of moraines in Peru and Bolivia substantiated the previously hypothesized local maximum extent as occurring early during the last glacial cycle, with a more diminutive extension during the global LGM (Smith et al, 2005). However, methodological differences in the application of TCN techniques (sampling, production rate choice, age calculation, and interpretation) have resulted in different interpretations of glaciation timing and paleoclimate forcing Glasser et al, 2009;Smith and Rodbell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Basal sediments from moraine-dammed lakes and peatlands in the Palcoco and Milluni valleys have radiocarbon ages that range from 12.8 to 10.9 ka (10.9 ± 0.1 to 9.6 ± 0.1 14 Cka) (Seltzer, 1992). Smith et al (2005) reported TCN ages of late glacial moraines that date from 19.4 to 10.3 ka.…”
Section: Cordillera Realmentioning
confidence: 99%
See 2 more Smart Citations